Hybridfügen – Eine Fügetechnik für den eigenschaftsoptimierten Leichtbau - Hahn, O.; Peetz, A.; Meschut, Gerson (Tagungsband zur Swiss Bondung ´99)

Auslegung und Fertigung von Klebverbindungen vor dem Hintergrund verbesserter Wärmeleitfähigkeit - Meschut, Gerson (Tagungsband zur Swiss Bondung ´99)

Kleben – eine innovative Fügetechnik für den Leichtbau - Meschut, Gerson (Tagungsband zur Vortragsveranstaltung “75 Jahre schweißtechnische Ausbildung in Braunschweig”)

Vermeidung fertigungsinduzierter Schädigungen beim Kleben dünnwandiger Stahlbauteile - Hahn, O.; Eis, M.; Meschut, Gerson (Tagungsband zum Dresdner Leichtbausymposium 1999)

Mechanische Eigenschaften stanzgenieteter und geklebter Aluminiumfeinbleche - Hahn, O.; Peetz, A.; Meschut, Gerson (Schweißen und Schneiden)

Prüfverfahren zur Ermittlung thermischer und reaktionsbedingter Volumenänderungen von Klebstoffen und Gießharzen - Hahn, O.; Walther, U.; Meschut, Gerson (Schweißen und Schneiden)

Curing caused tensions on adhesive bonding of steel sheets - Hahn, O.; Eis, M.; Meschut, Gerson (Welding in the World)

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)

Simple, Efficient Routing Schemes for All-Optical Networks - Flammini, Michele; Scheideler, Christian (Theory Comput. Syst.)

Locally Efficient On-Line Strategies for Routing Packets Along Fixed Paths - Berenbrink, Petra; Scheideler, Christian (SODA)

Simple Competitive Request Scheduling Strategies - Berenbrink, Petra; Riedel, Marco; Scheideler, Christian (SPAA)

Kontextuelle Disziplingeschichtsschreibung - Peckhaus, Volker; Thiel, Christian (Perspektiven der Disziplingeschichtsschreibung)

Partitioned neighborhood spanners of minimal outdegree - Fischer, Matthias; Lukovszki, Tamas; Ziegler, Martin (Proceedings of the 11th Canadian Conference on Computational Geometry)
A geometric spanner with vertex set P in Rd is a sparse approximation of the complete Euclidean graph determined by P. We introduce the notion of partitioned neighborhood graphs (PNGs), unifying and generalizing most constructions of spanners treated in literature. Two important parameters characterizing their properties are the outdegree k in N and the stretch factor f>1 describing the quality of approximation. PNGs have been throughly investigated with respect to small values of f. We present in this work results about small values of k. The aim of minimizing k rather than f arises from two observations: * k determines the amount of space required for storing PNGs. * Many algorithms employing a (previously constructed) spanner have running times depending on its outdegree. Our results include, for fixed dimensions d as well as asymptotically, upper and lower bounds on this optimal value of k. The upper bounds are shown constructively and yield efficient algorithms for actually computing the corresponding PNGs even in degenerate cases.

Fast Reconstruction of Delaunay Triangulations - Sohler, Christian (Proceedings of the 11th Canadian Conference on Computational Geometry ( CCCG'99))
We present a new ( O(n) ) algorithm to compute good orders for the point set of a Delaunay triangulation of ( n ) points in the plane. Such a good order makes reconstruction in ( O(n) ) time with a simple algorithm possible. In contrast to the algorithm of Snoeyink and van Kreveld cite1, which is based on independent sets, our algorithm uses a breadth first search (BFS) to obtain these orders. Both approaches construct such orders by repeatedly removing a constant fraction of vertices from the current triangulation. The advantage of the BFS approach is that we can give significantly better bounds on the fraction of removed points in a phase of the algorithm. We can prove that a single phase of our algorithm removes at least ( frac13 ) of the points, even if we restrict the degree of the points (at the time they are removed) to 6. We implemented and compared both algorithms. Our algorithms is slightly faster and achieves about 15% better vertex data compression when using a simple variable length code to encode the differences between two consecutive vertices of the given order.

Von der Geometrie zur Naturalisierung. Utopisches Denken im 18. Jahrhundert zwischen literarischer Fiktion und frühneuzeitlicher Gartenkunst. Hallesche Beiträge zur Europäischen Aufklärung Bd. 10

New Results on Geometric Spanners and Their Applications - Lukovszki, Tamás

New Results on Fault Tolerant Geometric Spanners - Lukovszki, Tamás (Proceedings of the 6th Workshop on Algorithms an Data Structures (WADS'99), LNCS)
We investigate the problem of constructing spanners for a given set of points that are tolerant for edge/vertex faults. Let S be a set of $n$ points in the d-dimensional space and let k be an integer number. A k-edge/vertex fault tolerant spanner for S has the property that after the deletion of k arbitrary edges/vertices each pair of points in the remaining graph is still connected by a short path. Recently it was shown that for each set S of n points there exists a k-edge/vertex fault tolerant spanner with O(k^2 n) edges which can be constructed in O(n log n + k^2 n) time. Furthermore, it was shown that for each set S of n points there exists a k-edge/vertex fault tolerant spanner whose degree is bouned by O(c^k+1) for some constant c. Our first contribution is a construction of a k-vertex fault tolerant spanner with O(kn) edges which is a tight bound. The computation takes O(n log^d-1 n + k n log log n) time. Then we show that the same k-vertex fault tolerant spanner is also k-edge fault tolerant. Thereafter, we construct a k-vertex fault tolerant spanner with O(k^2 n) edges whose degree is bounded by O(k^2). Finally, we give a more natural but stronger definition of k-edge fault tolerance which not necessarily can be satisfied if one allows only simple edges between the points of S. We investigate the question whether Steiner points help. We answer this question affirmatively and prove Theta(kn) bounds on the number of Steiner points and on the number of edges in such spanners.

Data management in networks: experimental evaluation of a provably good strategy - Krick, Christof; Meyer auf der Heide, Friedhelm; Räcke, Harald; Vöcking, Berthold; Westermann, Matthias (Proceedings of the eleventh annual ACM symposium on Parallel algorithms and architectures - SPAA '99)

Heiner Müller - Eke, Norbert Otto
Neuausgabe als E-Book: Stuttgart 2015

Juden und jüdische Kultur im Vormärz. Forum Vormärz Forschung. Jahrbuch 1998